1993
DOI: 10.1002/prac.19933350106
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity in [4+2] cycloadditions of new 4-trifluoromethyl-1,3-oxazin-6-ones: Access to functionalized 2-trifluoromethyl pyridines

Abstract: Recently discovered 4‐trifluoromethyl‐1,3‐oxazin‐6‐ones react with electron‐poor dienophiles as 2‐aza‐1,3‐dienes in Diels‐Alder cycloadditions to give new 2‐trifluoromethyl pyridines (3a–d, 4a–c). Regioselectivity is excellent in the case of unsymmetrical dienophiles. These new pyridines permit further useful transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Viehe and co-workers [9] prepared a series of 2-trifluoromethylpyridine derivatives by performing cycloaddition reactions between trifluoromethyl oxazinone and a variety of electronpoor alkynes whilst Schlosser reported that 1-ethoxy-3-trifluoromethyl-1,3-butadiene [10] underwent cycloaddition with a range of imines to give various trifluoromethylpyridine products.…”
Section: Introductionmentioning
confidence: 99%
“…Viehe and co-workers [9] prepared a series of 2-trifluoromethylpyridine derivatives by performing cycloaddition reactions between trifluoromethyl oxazinone and a variety of electronpoor alkynes whilst Schlosser reported that 1-ethoxy-3-trifluoromethyl-1,3-butadiene [10] underwent cycloaddition with a range of imines to give various trifluoromethylpyridine products.…”
Section: Introductionmentioning
confidence: 99%
“…Steglich [12] has suggested that a lower degree of reactivity and regioselectivity can be expected for 1,4-oxazin-2ones 3 as compared to 1,3-oxazin-6-ones 2, and Boger [21] suggests the reactivity of similar substituted 1,3-oxazin-6ones 2 is comparable to 1,2,4-triazines 1. A further example that adds confusion to the situation is that 1,3-oxazin-6ones 2 react with both electron-poor [19] and -rich [20,21] acetylenes to afford pyridines, depending on the substitu-in the unsubstituted cases 1,2,4-triazine is less reactive in comparison to 1,3-oxazin-6-one and 1,4-oxazin-2-one for both reaction modes, whereas the cycloaddition regioselectivities depend largely on the diene. For example, 1,3-oxazin-6-one leads to kinetic meta isomers, in comparison to 1,2,4triazine and 1,4-oxazin-2-one, which give rise to para isomers.…”
Section: Introductionmentioning
confidence: 99%